2010
DOI: 10.1111/j.1547-5069.2010.01345.x
|View full text |Cite
|
Sign up to set email alerts
|

Skipping Meals and Less Walking Among African Americans Diagnosed With Preterm Labor

Abstract: Pregnancy is a time when health professionals monitor women regularly and presents a unique opportunity for practitioners to communicate the importance of frequent meals and snacks throughout pregnancy, as well as the health benefits of walking as a form of physical activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…The study flow is summarized in Figure 1. Data were extracted from 90 studies ( n = 126,242), 17–19,30,38,39,45–105 with 23 studies containing multiple dietary intake assessment points during pregnancy ( n = 4,985) 11,12,33–37,40,106–120 . The countries represented by geographical region are the USA (26 studies, n = 12,765)/Canada (5 studies, n = 143), UK (19 studies, n = 15,653), Europe (27 studies, n = 93,395), Australia (5 studies, n = 2,557)/NZ (2 studies, n = 291), and Japan (6 studies, n = 1,438).…”
Section: Resultsmentioning
confidence: 99%
“…The study flow is summarized in Figure 1. Data were extracted from 90 studies ( n = 126,242), 17–19,30,38,39,45–105 with 23 studies containing multiple dietary intake assessment points during pregnancy ( n = 4,985) 11,12,33–37,40,106–120 . The countries represented by geographical region are the USA (26 studies, n = 12,765)/Canada (5 studies, n = 143), UK (19 studies, n = 15,653), Europe (27 studies, n = 93,395), Australia (5 studies, n = 2,557)/NZ (2 studies, n = 291), and Japan (6 studies, n = 1,438).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, most aforementioned components have been scarcely explored in pregnant women. A few epidemiological studies have reported that pregnant meal skippers may be at risk of preterm delivery [19,[79][80][81]. In particular, breakfast skipping in early pregnancy was associated with offspring obesity development through the first 12 years of life [82,83].…”
Section: Concluding Perspectivesmentioning
confidence: 99%
“…Additionally, it is essential to define both medical and social risk for PTB. Social risk for PTB encompasses one or more of the social determinants described in the literature associated with the condition, such as unstable housing (Behrman and Butler, 2007), food insecurity (Hennessey et al, 2009), exposure to stress and/or stressors (Hogue and Bremner, 2005;RichEdwards and Grizzard, 2005;Gennaro et al, 2008). Whereas medical risk factors for PTB include infections during pregnancy (Behrman and Butler, 2007;Manuck et al, 2016), a prior history of PTB (Behrman and Butler, 2007), preterm labor (Behrman and Butler, 2007), and a history of previous poor birth outcomes (Behrman and Butler, 2007;Bryant et al, 2010).…”
Section: Definitionsmentioning
confidence: 99%